FRI0123 Comparative effectiveness of subcutaneous versus intravenous tocilizumab in a pan-european collaboration of registries. (12th June 2018) - Lauper, K.; Santos, M.J.; Ianonne, F.; Rotar, Z.; Nordström, D.C.; Codreanu, C.; Kvien, T.K.; Kristianslund, E.K.; Pavelka, K.; Lukina, G.; Hernández, M.V.; et al.
Abstract : Background: In randomised controlled trials, subcutaneous tocilizumab (TCZ sc) has been found non-inferior to intravenous TCZ (TCZ iv) for the treatment of rheumatoid arthritis (RA) patients. However, to our knowledge, there are no observational studies comparing these two different routes of administration in routine care. Objectives: To compare the real-world effectiveness of TCZ sc and TCZ iv in RA patients. Methods: We included RA patients treated with TCZ from 8 European registries. We compared drug retention using Kaplan-Meier and Cox models. The proportions of patients achieving CDAI remission and low disease activity (LDA) at 1 year were compared using LUNDEX correction with computation of confidence intervals by bootstrapping. 1 Results: 2896 patients were retrieved from the collaborative registries before January 2017, including 2469 TCZ iv and 427 TCZ sc. Baseline demographics were similar between both groups, but patients in the TCZ iv group had a more severe disease activity, with higher DAS28, CDAI, tender joint count (TJC), swollen joint count (SJC), ESR and physician global assessment values (table 1). Crude median retention was 2.14 years (95% CI 2.03–2.33) for TCZ iv and 1.00 year for TCZ sc (95% CI 0.83–1.10), p<0.001. However, in a covariate-adjusted analysis, stratified by country- and year of treatment initiation, we found that hazards of discontinuation were similar among patients on TCZ iv compared to patients on TCZ sc (hazard ratio: 0.92, CI 95% 0.77–1.09). The average adjusted CDAI change at 1 year was −1.15 for TCZ iv, and −1.06 for TCZ sc patients (p-value of interaction between treatment group and time: 0.68). The average adjusted DAS28 change at 1 year was also similar between groups (−0.28 for TCZ iv and −0.09 for TCZ sc, p value of interaction: 0.21). CDAI remission and LDA at 1 year (LUNDEX corrected) were similar between TCZ sc and TCZ iv patients (CDAI remission: 9.5% in TCZ iv vs. 9.4% in TCZ sc (difference: −0.1%, bootstrap 95% CI: −3.8%>3.8%); CDAI LDA: 37.3% in TCZ iv vs.33.7% in TCZ sc (difference: −3.6%; bootstrap 95% CI: −9.4%; 2.5%)). Likewise, DAS28 remission and LDA at 1 year (LUNDEX corrected) were comparable between TCZ sc and TCZ iv (difference in DAS28 remission: −2.7%; bootstrap 95% CI: −8.8%; 3.5%; difference in DAS28 LDA: −5.8%; bootstrap 95% CI: −11.9%; 0.4%). Conclusions: Drug retention and clinical effectiveness, assessed by CDAI and DAS28 changes and responses, were similar in both groups of patients, treated with TCZ sc or TCZ iv. Reference: [1] Kristensen LE, et al. Arthritis Rheum2006;54:600–6. doi:10.1002/art.21570 Disclosure of Interest: K. Lauper: None declared, M. Santos: None declared, F. Ianonne: None declared, Z. Rotar: None declared, D. Nordström Grant/research support from: AbbVie, BMS, MSD, Pfizer, Roche and UCB, Consultant for: AbbVie, BMS, MSD, Roche, UCB and Pfizer, C. Codreanu: None declared, T. Kvien: None declared, E. Kristianslund: None declared, K. Pavelka Grant/research support from: AbbVie, Roche, Medis, MSD and Pfizer, Consultant for: AbbVie, Roche, Amgen, MSD, BMS, UCB and Egis, G. Lukina Consultant for: BMS, Roche, MSD, AbbVie and Pfizer, M. Hernández: None declared, S. Gale Employee of: Genentech, K. Sarsour Employee of: Genentech, Y. Luder Employee of: F. Hoffmann-La Roche, D. Courvoisier: None declared, C. Gabay Grant/research support from: Roche, AbbVie, MSD and Pfizer, Consultant for: AbbVie, BMS, Roche, Pfizer, Celgene, MSD, Janssen Cilag, Amgen, UCB